Implementasi projek penguatan profil pelajar pancasila di sekolah dasar - Sari, Anggia Murni Fajar; Istiyati, Siti; Surya, Anesa (Universitas Sebelas Maret, 2023)
This study aims to think about (1) the planning of the Pancasila Student Profile Strengthening Project in Class IV co-curricular activities at SD Ta'mirul Islam Surakarta, (2) its implementation, and (3) evaluation of the products produced. This study uses a case study methodology and is qualitative in nature. The data sources of this study include school principals, IVB class teachers and IVB class students of SD Ta'mirul Islam Surakarta. The subject retrieval technique used in this study is purposive sampling technique. Data collection is carried out by observation techniques, interviews, and document studies. The validity test of data used is the data triangulation technique (source) and the triangulation technique. The data analysis used is qualitative data analysis proposed by Cresswell. The results of this study are as follows: First, P5 planning is contained in a project module that has been designed by modification by the teacher together with a team of facilitators with components that are in accordance with the guidelines of the Ministry of Education and Culture. Second, the implementation of P5 is in accordance with the planned flow in the project module, namely from the stage of introduction, contextualization, action, reflection on action. Third, the evaluation is carried out by teachers on students through an assessment of the development of the dimensions of the Pancasila student profile with the results of reaching the level of development as expected and very developed as well as an assessment of the results of ecoprint products with an average value of 3.58 in the good category. Thus, it can be inferred that P5, a new paradigm in Indonesian education, can be used to cultivate character in accordance with the character dimensions of the Pancasila student profile, but only when P5 activities are conducted.